The Last Suffragist Standing: The Life and Times of Laura Marshall Jamieson - Kvill, Kesia (Labour / Le Travail, 2019)
The article reviews the book, "The Last Suffragist Standing: The Life and Times of Laura Marshall Jamieson," by Veronica Strong-Boag.